The origin, interrelationship and distribution of Southern African Rajidae (Chondrichthyes, Batoidei) - Hulley, Percy Alexander (Department of Biological Sciences, 2016)
The systematics of the Rajidae (skates) of southern Africa are revised, with a view to clearing up the confusion which now exists, and to forming a reliable basis for future biological studies. To date, some 150 - 160 species have been described for the genus Raja alone. The existing confusion probably results from the sexual dimorphism which occurs within the species and variation in form with growth. Modern methods advocate the use of characters, other than external features, the most reliable being the clasper anatomy, neurocranial structure and vertebral count, and these principles have been applied in the present revision.